2009
DOI: 10.1073/pnas.0812859106
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of the olfactory signaling system in the kidney

Abstract: Olfactory-like chemosensory signaling occurs outside of the olfactory epithelium. We find that major components of olfaction, including olfactory receptors (ORs), olfactory-related adenylate cyclase (AC3) and the olfactory G protein (Golf), are expressed in the kidney. AC3 and Golf colocalize in renal tubules and in macula densa (MD) cells which modulate glomerular filtration rate (GFR). GFR is significantly reduced in AC3 ؊/؊ mice, suggesting that AC3 participates in GFR regulation. Although tubuloglomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
217
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 203 publications
(226 citation statements)
references
References 37 publications
6
217
0
3
Order By: Relevance
“…ORs also play important roles outside of the OE, serving as specialized chemosensors in a variety of tissues (2,3). We have recently demonstrated that major components of the olfactory signaling pathway are present in the kidney, where they play important functional roles in the regulation of both glomerular filtration rate (GFR) and renin release (4). In addition to the olfactory G protein G olf and the olfactory adenylate cyclase AC3, we reported that at least six members of the OR gene superfamily are expressed in renal tissue.…”
mentioning
confidence: 99%
“…ORs also play important roles outside of the OE, serving as specialized chemosensors in a variety of tissues (2,3). We have recently demonstrated that major components of the olfactory signaling pathway are present in the kidney, where they play important functional roles in the regulation of both glomerular filtration rate (GFR) and renin release (4). In addition to the olfactory G protein G olf and the olfactory adenylate cyclase AC3, we reported that at least six members of the OR gene superfamily are expressed in renal tissue.…”
mentioning
confidence: 99%
“…Furthermore, ORs maintain up to 40% genetic similarity with rhodopsin (43). Additionally, ORs appear within areas of mammalian corpus that have no olfactory capacity (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). We therefore hypothesize that due to functional and morphological similarities, if ORs are activated through an ET mechanism, other GPCRs share the same fundamental mechanism.…”
mentioning
confidence: 99%
“…One of the novel renal G‐protein‐coupled receptors we are interested in is olfactory receptor 78 (Olfr78; Pluznick et al . 2009). Although our original intention was to study the role of Olfr78 in whole‐animal physiology, through the course of these studies we came to realize that the functional role of Olfr78 is intimately tied together with short‐chain fatty acid (SCFA) metabolites produced by the gut microbiota by breaking down complex dietary polysaccharides (Pluznick et al .…”
Section: Introductionmentioning
confidence: 99%